STRATEGI MANAJEMEN INFORMASI LAYANAN KESEHATAN DI RUMAH SAKIT - Biantara, Irgi; Dety Mulyanti (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
Hospitals certainly have strategic policy formulation in internal parts, especially organization, management and human resources (HR) and must be able to make decisions effectively to improve the quality of health services. So by increasing this vision, there is a need for an information management strategy in hospital services. The purpose of this literature review is to examine journals that explain health service information management strategies in hospitals. This literature review used articles in the PubMed, Google Scholar, and ProQuest databases published in 2017-2022, obtained 651 articles which were then reviewed using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) diagram and obtained 6 articles that met the requirements for analysis. . The results of 6 articles obtained that the health service information management strategy in hospitals is by increasing Human Resources (HR), optimizing Standard Operating Procedures (SOP), developing Hospital Management Information Systems (HMIS), Improving the Quality of Health Services, and Expansion of Promotion or Hospital Services. It can be concluded that the management information system in health services is something that integrates the entire process flow of hospital services in the form of a network that improves human resources for health services, quality information systems in hospitals. This strategy becomes an arrangement or equipment that provides information to develop to achieve the objectives of its activities